Social Status of Hook and Line Fishermen in Visakhapatnam - Immanuel, Sheela; G., Syda Rao (Fishery Technology, 2025)
This study aims to document the socio economic profile of the fisherfolk involved in hook and line fishing. The study was conducted among a sample of 100 fishermen involved in hook and line fishing in Pedajalaripeta village in Visakhapatnam district of Andhra Pradesh. Field survey method was adopted for data collection. Forty three percent of the fishermen were between the age group of 36- 45 years, and all of them belonged to Hindu religion and Jalari caste. Nearly 72% of the male population above the age of fifteen was also involved in hook and line fishing. The daily income of the fisherfolk was dependent on fish catch and it varied from Rs.150 to Rs.1 000. Regarding the ownership pattern, 32% owned fibre catamaran and 9% owned wooden catamaran. The important types of hook and line operated in the area were long line and hand line. Only single day fishing trips were operated in the study area. In 28% of the families, the fisherwomen were involved in fish marketing and their monthly income ranged from Rs. 3 000 to Rs. 7 500. Poor implementation of regulations and excess fishing capacity were reported as major constraints. The study also suggests ways to improve the socio economic status of hook and line fishermen.